The Gold Mine Effect - How to find undervalued talent - Ankersen, R. (2012)
For six months Rasmus Ankersen (www.rasmusankersen.com) has travelled around the world to crack the secrets of the world's best performance hotbeds. In this video he explains how you can improve your ability to spot undervalued talent.